INOVATTION PROMMAGE OF MINERAL BLOCK ANIMAL FEED OF ACI KAWUNG WASTE IN BINA MANDIRI LIVESTOCK GROUP IN PULOSARI VILLAGE, WEST JAVA. - Emmia Tambarta Kembaren; Mawardati; Baidhawi; Jalin Atma Islamy; Nepo Erbianto; Aulia Rahman (RADJA PUBLIKA, 2024)
The population of Indonesia is exhibiting a constant annual growth. The latest Indonesian statistical data, from 2023, indicates that the population of Indonesia has exceeded 267 million. As a consequence of the considerable population growth, there is an increasing demand for food. One of the most significant sources of protein is animal protein, which can be derived from cattle, sheep, goats, fish, and other sources. The Elang Bodas Program represents a social innovation initiative spearheaded by CSR Community Empowerment of PT PLN Indonesia Power PLTP Gunung Salak UBP Kamojang Year 2024. The program's core objective is to enhance the efficiency and sustainability of the livestock sector in Pulosari Village. The innovation of this programme is evident at the system level. The methodology employed to address the challenges encountered comprises the following activities: (1) theoretical training (classroom-based) on the production of feed using mineral block technology, (2) direct practical experience conducted by partners under the guidance of the team, and (3) mineral block case study. The efficacy of the programme is evidenced by a notable increase in livestock weight, with an average gain of 6 kilograms observed in the experimental group compared to the control group, which did not receive similar treatment. The economic effectiveness of the programme demonstrates an additional profit of Rp. 1,700,000 per head per year. The results demonstrate that the assets have been employed in an optimal manner throughout the implementation of the Elang Bodas programme. The time effectiveness of the programme can be observed in the alterations to the timeframes involved in the provision of animal feed. The environmental impact of the programme is evidenced by the utilisation of kawung aci waste as a raw material for the production of alternative mineral block feed, which has economic value. The programme has been observed to have a significant impact on the acquisition of knowledge and skills amongst the members of the Bina Mandiri Farmer Group, with an increase of 100% in the knowledge and abilities of 38 individuals. The impact of the programme on behavioural change demonstrated that 52% of participants exhibited a willingness to adopt the technology.